Law Counseling and English Language Training for the Purpose of Overseas Traveling for High School Students in Tangerang Regency - Feronica Feronica; Stephanus D. Prastianto; David Wijaya (MITRA: Jurnal Pemberdayaan Masyarakat, 2017)
This community service program is motivated by a number of incidents that have befallen Indonesian citizens staying abroad. Most of the cases could be attributable to one single factor: the lack of information about the rules and regulations in the foreign country. This lack could have been compensated by requesting for consular assistance from the local KBRI (the Indonesian Embassy) or KJRI (the Indonesian Consul General) as well as getting information from the local citizens. This activity is done to High School Grade 3 students because after graduating from high school they have an opportunity to go abroad, either to continue education, work, or for recreation. By providing legal counseling and English training they will be better prepared if the plan to go the country is done. The method employed in this program was providing counsel to Indonesian citizens on the roles of KBRI and KJRI as well as instruction on useful English expressions that they will need if they are involved in any incidents in another country. This program was effective as the target participants were the twelfth-grade students who might want to go abroad for a number of reasons such as studying, working or going on vacation. It took place in the Tangerang Regency, the province of Banten, where such program had never been provided for the participants. It is suggested that future programs should include simulations and role plays, e.g. talking to immigration officers in a foreign country.